Japan's Holy War : The Ideology of Radical Shinto Ultranationalism - Skya, Walter (Book collections on Project MUSE., 2009)
"This is a work of history documenting the late 19th- and early 20th-century transformation of State Shinto into a radical ideology that ultimately drove Japan into a holy war against Western civilization."--Provided by publisher